Uji Aktivitas Antibakteri Ekstrak Etanol Daun Jambu Biji (Psidium Guajava L.) Terhadap Shigella dysenteriae ATCC 13313 - Irma Tia Trinanda; Dani Prasetyo; Desti Kameliani (JCPS (Journal of Current Pharmaceutical Sciences), 2025)
Bloody diarrhea, also known as bacterial dysentery, is caused by Shigella dysenteriae bacteria. One potential treatment fot dysentery involves the use of guava leaves (Psidium guajava L.). The aim of this study was to determine the secondary metabolite compounds contained in the ethanol extract of guava leaves and to evaluate its antibacterial activity against Shigella dysenteriae ATCC 13313. The secondary metabolite compounds were identified through phytochemical screening by observing color changes after mixing the ethanol extract of guava leaves with specific reagents. The antibacterial activity was tested using the paper disc diffusion method with extract concentrations of 10%, 25%, and 40%. Antibacterial activity was indicated by the formation of a clear inhibitor zone around the paper discs. The results showed that guava leaf extract contains secondary metabolites such as flavonoids, saponins, tannins and alkaloids, which contribute to bacterial growth inhibition. The antibacterial activity of the extract showed that the 40% extract concentration exhibited the largest inhibition zone (15,33 mm), which is categorized as strong antibacterial activity.